Nanomaterials as efficient platforms for sensing DNA. (September 2019) - Vikrant, Kumar; Bhardwaj, Neha; Bhardwaj, Sanjeev K.; Kim, Ki-Hyun; Deep, Akash
Abstract: The advent of modern biomedical science has led to various accomplishments such as the early detection of genetic disorders. To pursue further advancement in this field, the development of highly specific, sensitive, and economical probes for DNA may be an emerging imperative. Due to the diverse merits of nanomaterials (e.g., cost-effective, rapid, and precise detection capabilities with improved detection limits), nanomaterial technology has made itself a viable option for designing new and advanced sensors. At present, the techniques for sensing DNA are primarily based upon biosensing approaches. This review article highlights the recent developments in nanotechnology as a potential platform for the detection of DNA. We further identify the present bottlenecks and future scope for the advancement of nanostructure-based DNA sensors and describe the research needs in associated areas. Graphical abstract: Image 1033